CONTENT MANAGEMENT SYSTEM FOR SCHOOL INFORMATION WEBSITE - Muhammad Yani; Fahru Rizal; Muhammad Reza Padillah (Universitas Mulia, 2021)
The website is one of the digital information media used by schools to display their profiles so that they can be known by the public. Some SMP Negeri in Kota Samarinda do not yet have a website as a media or school information center. This could be due to difficulties in creating and on the website of each school. From these problems, in this study researchers innovated to create a Content Management System (CMS) for school websites, especially at SMP Negeri 29 Samarinda. Laravel PHP framework is used with the system development method is the Waterfall method.